2013
DOI: 10.1038/cddis.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-containing protein regulates the proteasome-mediated degradation of DNA-PKcs in glioma cells

Abstract: DNA-dependent protein kinase (DNA-PK) has an important role in the repair of DNA damage and regulates the radiation sensitivity of glioblastoma cells. The VCP (valosine-containing protein), a chaperone protein that regulates ubiquitin-dependent protein degradation, is phosphorylated by DNA-PK and recruited to DNA double-strand break sites to regulate DNA damage repair. However, it is not clear whether VCP is involved in DNA-PKcs (DNA-PK catalytic subunit) degradation or whether it regulates the radiosensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
(62 reference statements)
1
32
0
Order By: Relevance
“…VCP is a member of the AAA class of ATPases, found predominantly in the cytoplasm, and involved in diverse biological processes, including endoplasmic reticulumassociated degradation and ubiquitin fusion degradation (47). Knockdown of VCP in glioblastoma cells led to accumulation of DNA-PKcs and resistance to ionizing irradiation, ultimately resulting in shorter survival times in an orthotopic xenograft mouse model (46). This study supports the importance of regulation of DNA-PKcs ubiquitination in the cytoplasm.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…VCP is a member of the AAA class of ATPases, found predominantly in the cytoplasm, and involved in diverse biological processes, including endoplasmic reticulumassociated degradation and ubiquitin fusion degradation (47). Knockdown of VCP in glioblastoma cells led to accumulation of DNA-PKcs and resistance to ionizing irradiation, ultimately resulting in shorter survival times in an orthotopic xenograft mouse model (46). This study supports the importance of regulation of DNA-PKcs ubiquitination in the cytoplasm.…”
Section: Discussionsupporting
confidence: 69%
“…Additional experiments will be needed to address these interesting questions. During our manuscript preparation, Jiang et al (46) showed that DNA-PKcs is ubiquitinated and bound to valosincontaining protein (VCP), possibly for regulation of proteasomedependent degradation. VCP is a member of the AAA class of ATPases, found predominantly in the cytoplasm, and involved in diverse biological processes, including endoplasmic reticulumassociated degradation and ubiquitin fusion degradation (47).…”
Section: Discussionmentioning
confidence: 99%
“…hDAAO‐EYFP; Fig. B) suggesting that it enhances degradation processes mediated by the UPS in a compensatory way, as previously reported for different proteins . An increasing body of evidence suggests that cross‐talk between the UPS and the lysosome system does exist and consists of a sharing of some of the ubiquitin‐recognizing molecules or shuttle factors: cells respond to blockage of the UPS by up‐regulating macroautophagy, whereas a persistent halt of macroautophagy has been shown to affect UPS activity .…”
Section: Discussionmentioning
confidence: 90%
“…Recruited by the heterodimer of Ku70/Ku80 to DSBs, DNA-PKc (DNA-dependent protein kinase, catalytic subunit) phosphorylates and alters the activity of many proteins, including itself, to mediate DNA repair through the NHEJ pathway (16). Like most other eukaryotic intracellular proteins, both Ku70 (17) and DNA-PKc (18) are degraded via the ubiquitin-proteasome system, in which proteins are tagged by ubiquitin and then degraded by the 26S proteasome complex. In pertinent studies, the proteasome inhibitor MG132 significantly prolonged the half-lives of those DNA repair proteins in cultured cells.…”
mentioning
confidence: 99%